Highly Effective Pt-Co/ZSM-5 Catalysts with Low Pt Loading for Preferential CO Oxidation in H2-Rich Mixture - Marina Shilina; Irina Krotova; Sergey Nikolaev; Sergey Gurevich; Denis Yavsin; Olga Udalova; Tatiana Rostovshchikova (Hydrogen, 2023)
New Pt-Co catalysts of hydrogen purification from CO impurities for fuel cells were fabricated via the deposition of monodispersed 1.7 nm Pt nanoparticles using laser electrodispersion on Co-modified ZSM-5 prepared by the Co(CH3COO)2 impregnation. The structure of prepared Pt-Co zeolites was studied by low-temperature N2 sorption, TEM, EDX, and XPS methods. The comparative analysis of samples with different Pt (0.01–0.05 wt.%) and Co (2.5–4.5 wt.%) contents on zeolites with the ratio of Si/Al = 15, 28, and 40 was performed in the CO-PROX reaction in H2-rich mixture (1%CO + 1%O2 + 49%H2 + 49%He). The synergistic catalytic action of Pt and Co on zeolite surface makes it possible to completely remove CO from a mixture with hydrogen in a wide temperature range from 50 to 150 °C; the high efficiency of designed composites with low Pt loading is maintained for a long time. The enhancement of PROX performance originates from the formation of new active sites for the CO oxidation at the Pt-Co interfaces within zeolite channels and at the surface. In terms of their activity, stability, and selectivity, such composites are significantly superior to known supported Pt-Co catalysts.